RESPONSABILIDADE SOCIAL EMPRESARIAL:discursos e práticas sobre a diversidade - Teixeira, Kamila Cristina da Silva (2014)
This study aims to analyze corporate actions with a gender and sexual orientation, seeking to understand them within the framework of the Brazilian social protection system. In this sense, our proposal is to defend the thesis that the performance of the business together with historically discriminated groups, especially women and LGBT, conforms emerges when the debate in the country that emphasizes the need to expand the activities of the welfare society in solving social problems. It is at this point that reaffirm traditional ties between state and civil society in shaping ways to boost social inclusion. This reaffirmation occurs both recovering traditional traits such as political and operational innovations. In methodological treatment, we conducted a qualitative study with a sample of eighteen companies from various industry sectors, public and private. We also analyze the performance of the Commission for Equal Opportunity Gender, Race and Ethnicity of Persons with Disabilities and to Combat Discrimination of the Ministry of Labour and Employment. As an instrument of data collection, the study of the companies split into two stages: the first featured documentary analysis and semi-structured interviews in three companies, and the second with documentary research conducted on sites of fifteen other companies on the internet. As for collecting data from the Commission, we conducted semi-structured interviews and documentary research